Design and evaluation of a mobile application for interactive reading - Mejías Rojas, Jose Andrés (2022)
Interactive reading of children’s books is one of the most effective methods for promoting language development in children. However, there are barriers for low-income families to purchase children's books. Therefore, we propose a mobile application that supports interactive reading between caregivers and young children, thus facilitating access to children's books for those families. This work reports on the design, development, and evaluation of the mobile application prototype. The mobile prototype was evaluated by six experts in interactive reading and the results suggest that our prototype can effectively support this process. Some usability issues were also found during the evaluation. We discuss how the mobile app aligns with four pillars of learning: active involvement, engagement, meaningfulness, and social interaction. Future directions on how to improve and extend our app are provided.